(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of knowledge, attitudes, and practices regarding Dengue hemorrhagic fever control among residents of Long Ho district, Vinh Long province in 2025, and to analyze related influencing factors. Subjects and Methods: A descriptive cross-sectional study combining both quantitative and qualitative approaches was conducted among 420 household heads or representatives aged 18 years and older, along with 18 key community stakeholders. Data collection included structured questionnaires, direct household observations, and in-depth interviews with influential individuals involved in Dengue prevention. Results: The proportions of residents with correct knowledge, attitudes, and practices were 67.9%, 77.9%, and 57.9% respectively. Statistically significant correlations were observed between knowledge, attitudes, and practices (p < 0.05). Educational level had an important influence on knowledge and practice; occupation and age group affected attitudes and practices. Correct knowledge was associated with correct attitudes, and both contributed to appropriate practices. Conclusion: While residents demonstrated relatively good knowledge and attitudes, their practical application in Dengue fever prevention was still limited. It is necessary to diversify health communication strategies to enhance community awareness, especially through regular vector control campaigns. Promoting the role of community organizations and influential individuals will help foster positive attitudes and sustainable prevention practices at the local level.